The Impact of Online Feedback Tools on EFL Learners Writing Skill Second Improvement Case of Year EFL Students at Mohamed Cherif Messaadia University ˒Souk- Ahras. - Mezahdia, Chorok (My University, 2023)
Abstract The current study aims to investigate the impact of online feedback tools in improving students writing in the Department of English Language, Mohamed Cherif Messaadia University, Souk-Ahras. To test the main hypothesis that suggests the possibility of enhancing writing skill proficiency through the use of online tools for feedback, two instruments had been used students questionnaire and teacher interview. The students’ questionnaire was provided to second- year (License, Master, Doctorate) students, and a semi- structured interview were conducted with three EFL teachers’ of written expression. The gathered data was analyzed quantitatively and qualitatively, it illustrated that students face several challenges while writing, one of this challenges is lack of vocabulary, and they are not familiar with grammatical rules enough, which led to committing different types of mistakes. As a result, they have used multiple Automated Corrective Feedback systems such as grammarly, varocco, and Hemingway editor to enhance student writing proficiency and decrease their errors. Automated corrective feedback was suggested to students as an alternative to teachers’ feedback. The obtained findings confirm the proposed hypothesis and give insights into a several suggestions that can help the student to develop their writing skill. ----------------------- ملخص تهدف الدراسة الحالية إلى التحقيق في تأثير برامج التصحيح الالكترونية عبر الإنترنت في تحسين كتابة الطلاب في قسم اللغة الإنجليزية، جامعة محمد الشريف مساعديه، سوق أهراس. لاختبار الفرضية الرئيسية التي تشير إلى إمكانية تعزيز إتقان مهارات الكتابة من خلال استخدام الأدوات الإلكترونية للتعليقات، تم استخدام أداتين لاستبيان الطلاب ومقابلة. تم تقديم استبيان لطلاب السنة الثانية جامعي.LMD، أجريت مقابلة شبه منظمة مع ثلاثة معلمين من EFL " تم تحليل البيانات التي تم جمعها من الناحية الكمية والنوعية، وأوضحت أن الطلاب استخدموا أنظمة تعليقات تصحيحية متعددة مؤتمنة من أجل تعزيز كفاءتهم في الكتابة وتقليل أخطائهم. تم اقتراح التعليقات التصحيحية الآلية للطلاب كبديل لتعليقات المعلمين. لذلك، تؤكد النتائج التي تم الحصول عليها الفرضية المقترحة وتعطي رؤى لعدد من الاقتراحات التي يمكن أن تساعد الطالب على تطوير مهارته في الكتابة. ------------------- RÉSUMÉ La présente étude vise à étudier l’impact des outils de rétroaction en ligne dans l’amélioration de la rédaction des étudiants dans le département de langue anglaise, Mohamed Cherif Messaadia Université, Souk-Ahras. Pour tester l’hypothèse principale qui suggère la possibilité d’améliorer les compétences en rédaction par l’utilisation d’outils électroniques pour la rétroaction, deux instruments ont été utilisés questionnaire des élèves et entrevue des enseignants. Le questionnaire des étudiants a été remis aux étudiants de deuxième année de DFA, et une entrevue semi-structurée a été menée auprès de trois enseignants d’EFL en compréhension écrite. Les données recueillies ont été analysées quantitativement et qualitativement, ce qui montre que les étudiants ont utilisé plusieurs systèmes de rétroaction corrective automatisés afin d’améliorer leurs compétences en rédaction et de réduire leurs erreurs. La rétroaction corrective automatisée a été suggérée aux élèves comme solution de rechange à la rétroaction des enseignants. Ainsi, les résultats obtenus confirment l’hypothèse proposée et donnent des idées à un certain nombre de suggestions qui peuvent aider l’étudiant à développer ses compétences en rédaction.